2013
DOI: 10.1186/1471-2288-13-135
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on neurological patient registries: a literature review and focus group study

Abstract: BackgroundPatient registries represent a well-established methodology for prospective data collection with a wide array of applications for clinical research and health care administration. An examination and synthesis of registry stakeholder perspectives has not been previously reported in the literature.MethodsTo inform the development of future neurological registries we examined stakeholder perspectives about such registries through a literature review followed by 3 focus groups comprised of a total of 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…Focus group participants also expressed differing views regarding the mode of data collection, with some patients preferring mailed surveys while others preferred to have data collection coincide with their medical appointments. These findings support prior research that highlights patient preferences and demands of study participation as perceived barriers to patient participation in research (17,19,20). Importantly, Robiner et al (21) found significant correlation between protocol adherence and perceived barriers such as missing work, frequency of appointments/procedures, number of appointments/procedures, and access to study location in 978…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Focus group participants also expressed differing views regarding the mode of data collection, with some patients preferring mailed surveys while others preferred to have data collection coincide with their medical appointments. These findings support prior research that highlights patient preferences and demands of study participation as perceived barriers to patient participation in research (17,19,20). Importantly, Robiner et al (21) found significant correlation between protocol adherence and perceived barriers such as missing work, frequency of appointments/procedures, number of appointments/procedures, and access to study location in 978…”
Section: Discussionsupporting
confidence: 83%
“…In a 2006 study among elderly patients with cancer, researchers found that endorsement and conversely discouragement from a patient's doctor was one of the most important influences on a patient's decision to enroll in a clinical trial (16). Similar views were expressed in a focus group among a Canadian population of patients with neurologic conditions (17). If a trusted provider presents a registry research opportunity to a patient and endorses it as both safe and of scientific value, the patient may be more inclined to join the registry, compared to when information about the registry is conveyed through other means.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…92 Privacy concerns include the risk of data falling into the hands of employers and health insurance companies. 92 Patients with more severe conditions like ALS appeared to have less reluctance about sharing their medical information, which may reflect a sense of urgency for research to develop meaningful treatment options in these more severely affected patients.…”
mentioning
confidence: 99%